Log moisture capacity does not predict epixylic bryophyte growth under thinned and unthinned forest canopies. (10th April 2017) - Haughian, Sean R.; Frego, Katherine A.
Summary: Coarse woody debris (CWD) serves as habitat for diverse and rare taxa in forest systems. Because the abundance of mosses appears to be correlated with log size and stage of decay, many have suggested that CWD serves as a moisture reservoir, ensuring a humid microclimate and facilitating moss growth, but no one has tested this connection. Intact forest canopies are also thought to maintain humid conditions that benefit moss growth. If microclimatic regulation is the primary mechanism contributing to high moss abundance on CWD, then epixylic moss growth should increase with the capacity of the log moisture reservoir, and the importance of the reservoir size should increase with canopy opening. Three types of synthetic logs, identical in size and shape but differing in moisture capacity, and two natural substrates, well‐decayed birch and cedar logs, were used to test the effects of log moisture capacity on growth of Dicranum flagellare under thinned and intact canopies of a spruce plantation over 20 months. Surface humidity was positively associated with moisture capacity, but did not reach the water compensation point outside of precipitation events. Under a closed forest canopy, moss growth was negligible across all log types. Under an open forest canopy, moss growth was greater on natural substrates than synthetic ones, and negatively related to moisture capacity. Coarse woody debris facilitates a sufficiently humid surface for only a short time after precipitation, presumably when a film of liquid water is maintained near the surface. For D. flagellare, canopy condition is a more accurate predictor of growth than CWD‐moisture capacity; any beneficial properties of CWD appear to be lessened by a dense forest canopy (as in silvicultural plantations), probably because it reduces access to liquid water from precipitation. We propose that the surface moisture availability of CWD depends on optimal depth of a 'resisting layer' below the log surface, representing a tradeoff between water retention and loss (via percolation or runoff at extremely deep vs. shallow resisting layer depth). Coarse woody debris may possess microclimate‐regulating traits that benefit moss growth, but it does not appear to act as a moisture capacitor. A lay summary is available for this article. Abstract : Lay Summary